A transliteration prototype using assistive technology and sign modelling. Issue 6 (18th August 2017) - Verma, Vivek K; Srivastava, Sumit
Abstract: This paper presents working of a prototype for automatic transliteration with Linguistic Modelling of Indian Sign Language (ISL). The implementation domain of the corpus is a banking system in the Indian environment. We have taken the corpus of Indian banking system from data-driven research groups working on sign dictionary of ISL. In preliminary evaluation we explored generation of phonological and morphological structure of ISL. Linguistic analysis has provided rich descriptions of sign language structure at the phonological, lexical, and syntactic levels.